The Effects of Surface Curvature on Cartilage Behaviour in Indentation Test: A Finite Element Study - Abd Latif, M.J.; Hashim, N.H.; ramlan, roszaidi; Mahmud, J.; Jumahat, A.; Abdul Kadir, M.R. (2013)
Computational modelling of the behaviour of articular cartilage is important in order to improve the understanding of disease processes such as arthritis, and the suitability of biomaterials in surgical treatment. In previous computational studies, the cartilage surface of axisymmetric models was assumed to be flat in order to evaluate the cartilage behaviour. This assumption was inappropriate since the synovial joint possessed curvature geometrical shape and may contribute to inaccurate results. Therefore, this study aims to examine the effects of the cartilage surface curvature to the cartilage behavior in indentation test using finite element analysis. Axisymmetric biphasic poroelastic finite element models of flat and various cartilage surface radii, including both concave and convex shapes of the curve, were generated to simulate creep indentation test in order to investigate possible effect to the contact stress and pore pressure of the cartilage. Based on the results, the smaller cartilage surface of 10 mm radius produced higher difference of the cartilage behaviour where it generated 39% difference in pore pressure and 6% difference in contact stress, compared to the flat cartilage. This could indicate that the cartilage curvature does affect the cartilage behavior in indentation test particularly the pore pressure of cartilage.